Antibiofilm and Immune-Modulatory Activity of Cannabidiol and Cannabigerol in Oral Environments—In Vitro Study (2024)
ABSTRACT: Objective: To evaluate the in vitro antimicrobial and antibiofilm properties and the immune modulatory activity of cannabidiol (CBD) and cannabigerol (CBG) on oral bacteria and periodontal ligament fibroblasts (PLF). Methods: Cytotoxicity was assessed by propidium iodide flow cytometry on fibroblasts derived from the periodontal ligament. The minimum inhibitory concentration (MIC) of CBD and CBG for S. mutans and C. albicans and the metabolic activity of a subgingival 33-species biofilm under CBD and CBG treatments were determined. The Quantification of cytokines was performed using the LEGENDplex kit (BioLegend, Ref 740930, San Diego, CA, USA). Results: CBD-treated cell viability was greater than 95%, and for CBG, it was higher than 88%. MIC for S. mutans with CBD was 20 µM, and 10 µM for CBG. For C. albicans, no inhibitory effect was observed. Multispecies biofilm metabolic activity was reduced by 50.38% with CBD at 125 µg/mL (p = 0.03) and 39.9% with CBG at 62 µg/mL (p = 0.023). CBD exposure at 500 µg/mL reduced the metabolic activity of the formed biofilm by 15.41%, but CBG did not have an effect. CBG at 10 µM caused considerable production of anti-inflammatory mediators such as TGF-β and IL-4 at 12 h. CBD at 10 µM to 20 µM produced the highest amount of IFN-γ. Conclusion: Both CBG and CBD inhibit S. mutans; they also moderately lower the metabolic activity of multispecies biofilms that form; however, CBD had an effect on biofilms that had already developed. This, together with the production of anti-inflammatory mediators and the maintenance of the viability of mammalian cells from the oral cavity, make these substances promising for clinical use and should be taken into account for future studies.